The Symbolic Meaning of the Molelase (Belly Rubbing) Traditional Procession Among the Tialo Ethnic Group in Tomini - Siti Nurmawlidah; Syamsuddin Syamsuddin; Mardiah Mardiah (Yayasan Kyadiren, 2025)
This study aims to describe the symbolic meanings of the Molelase (belly rubbing) tradition among the Tialo ethnic group in Tomini, Parigi Moutong Regency. This tradition serves as a ritual of prayer and protection for pregnant women and their fetuses at seven months of gestation to ensure a smooth delivery process. The research utilizes a qualitative method, with data collected through observation, interviews, and documentation. Data analysis follows an interactive model consisting of data reduction, data display, and conclusion drawing. The results identify eleven primary symbols in the Molelase procession: (1) awar-awar leaves, (2) turmeric leaves, (3) green ti leaves, (4) red ti leaves, (5) kalanchoe leaves, (6) palmyra palm leaf string, (7) black hen, (8) coins, (9) candles and matches, (10) knife, and (11) white rice. Those elements represent pleas for protection against evil spirits, physical strength during childbirth, and the hope for prosperity for the child.